NPK Fertilizer Effects on Growth and Flowering of Chinese Carnation - Owain, Mazin Amer (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of varying levels of NPK chemical fertilizers on the growth and flowering of the Chinese carnation plant (Dianthus chinensis). Conducted during the 2022–2023 academic year at the University of Tikrit's College of Agriculture, the experiment utilized a randomized complete block design (RCBD) with four treatments: no fertilizer, high nitrogen (47% N), high phosphorus (41% P), and high potassium (43% K). Key growth metrics, including plant height, leaf count, total chlorophyll content, flower count, and floral dimensions, were measured. Results indicated significant differences between treatments. High potassium fertilizer resulted in superior vegetative growth, with the highest leaf count (38.17 leaves per plant), wet weight (28.74 g per plant), and dry weight (6.05 g per plant). It also produced the most flowers (10.66 per plant). High nitrogen fertilizer notably increased chlorophyll content (12.14 mg/g wet weight), enhancing photosynthesis efficiency. These findings demonstrate that targeted nutrient application can optimize growth and flowering in Dianthus chinensis, with high potassium levels being particularly effective. The implications of this study suggest that precise NPK management can enhance ornamental plant production, contributing to horticultural practices and commercial flower cultivation. Future research should explore the long-term effects of these fertilizers and their environmental impact.